PERTARUNGAN SIMBOL KOMUNIKASI POLITIK DALAM PILKADA KABUPATEN LOMBOK UTARA - MUHAMMAD SYAOKI; MUHAMMAD FIKRI (TASÂMUH, 2020)
Regional election (Pilkada) is a stage for each candidate to attract public attention. The process is carried out in various ways. This includes the use of symbols. This study seeks to see the use of symbols as a political communication strategy in the Regional election of Lombok Utara Regency. The results of this study indicate that the regent candidates who are competing in the election of Lombok Utara Regency (KLU) use various symbols to attract the attention of voters. These include the use of taglines, gestures, and political attributes such as the words SANGGUP, S14P, fist, and respect. Symbol warfare is also carried out in the use of attributes attached to ballot photos. Apart from being aimed at attracting voters' interest, this symbol war is also used as a political communication strategy so that it is easy to remember in the election process.